2005
DOI: 10.2320/matertrans.46.2413
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Properties of Zn–Sn Alloys as High Temperature Lead-Free Solder on Cu Substrate

Abstract: The potentials of the newly designed Zn-xSn (x ¼ 40, 30, and 20 mass%) alloys as high temperature lead-free solders and their interface properties on Cu substrate were investigated, focusing on the interface microstructure and mechanical properties. Hypereutecic alloys show two endothermic peaks in differential scanning calorimetry (DSC), one appears at 200 C and the other varies from 365 to 383 C with decreasing Sn content. These peaks are well associated with the eutectic and liquidus temperatures of binary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 14 publications
3
41
0
Order By: Relevance
“…For this reason, several studies on Zn-(Sn, Al, Mg, Ga) based high temperature solders have been reported. [10][11][12][13][14] Vianco defined an ultra high temperature solder working properly between 573 K and 623 K and suggested a Zn-Al based alloy for the possible alloy system. 15) It has been reported the tensile strength, creep resistance, dimensional stability and corrosion resistance of Zn alloy are improved by the addition of Al/Cu elements.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, several studies on Zn-(Sn, Al, Mg, Ga) based high temperature solders have been reported. [10][11][12][13][14] Vianco defined an ultra high temperature solder working properly between 573 K and 623 K and suggested a Zn-Al based alloy for the possible alloy system. 15) It has been reported the tensile strength, creep resistance, dimensional stability and corrosion resistance of Zn alloy are improved by the addition of Al/Cu elements.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 show the interfacial regions of the Cu/Zn and Cu/ Ag joints, indicating that CuZn 5 and Cu 5 Zn 8 IMCs formed at the interface of Cu/Zn joints. Corresponding to relevant reports about Zn based solder joints, 12,[18][19][20] CuZn 5 was close to Zn and Cu 5 Zn 8 was adjacent to Cu substrate. In contrast, no distinct interdiffusion layers or IMCs could be observed at the Cu/Ag interface.…”
Section: Methodsmentioning
confidence: 64%
“…2B) (Moser et al, 1985), has been studied. This alloy system has the advantages of excellent thermal conductivity and mechanical properties (ductility and high ultimate tensile strength) and oxidation resistance in high-temperature highhumidity conditions (Lee et al, 2005;Santos et al, 2014). However, in addition to the corrosion problem due to zinc, there is a serious problem that the solidified solder joint returns to a solid+liquid mixed phase at the secondary reflow temperature (~250 o C), which is higher than the eutectic temperature of 199 o C (Fig.…”
Section: Candidates For High-temperature Pb-free Soldersmentioning
confidence: 99%
“…Nevertheless, Suganuma et al (2009) suggested that this hypereutectic alloy can be used as a high-temperature solder by controlling the liquid fraction at the secondary reflow temperature. They reported that the volume expansion caused by formation of the liquid phase (remelting) in the solder joint is not large enough to distort the bonding structure if the Sn content is <30 wt% (Lee et al, 2005). Table 1 summarizes the advantages and disadvantages of high-temperature Pb-free solder candidates.…”
Section: Candidates For High-temperature Pb-free Soldersmentioning
confidence: 99%